Development of pH Measuring Strip Test Based On West Kalimantan Local Plant - Aprianus Aril; Masriani Masriani; Husna Amalya Melati (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
Synthetic acid-base indicators possess some disadvantages. Therefore, it is necessary to develop a natural acid-base indicator made from a mixture of plant extracts, which has a strip form, is safe, eco-friendly, has a wide pH range, and has clear color changing. This research aims to determine the pH range, make a pH indicator in the strip form, and produce a biodegradable acid-base indicator made from a mixture of Melastoma malabathricum flower, Dioscorea alata rhizome, Syzygium paniculatum leaves, Garcinia fruit peel, Eleutherine bulbosa rhizome extracts. Plant extracts were obtained using the maceration method. pH range was evaluated using the visual method by sensing the color changing in the pH range from 1 to 14. pH indicator strip was made by applying filter paper in the strip form into the extract mixture for 2 hours. The biodegradable property of acid-base indicator strips was established by measuring indicator strip degradation after planting it in the ground for 20 days at room temperature. The results showed that the acid-base indicator strip made from a mixture of plant extracts was able to give a color change from pink to light green in the pH range of 3-8 and can be decomposed completely after planting it in the ground for 20 days. Thus, it indicated that a natural pH indicator strip based on West Kalimantan plants has the potential to be developed as a safe and effective acid-base indicator to substitute synthetic acid-base indicators.